Systemic Effects by Intrathecal Administration of Triamcinolone Acetonide in Patients With Multiple Sclerosis - Hoeflich, Andreas; Fitzner, Brit; Walz, Christina; Hecker, Michael; Tuchscherer, Armin; Bastian, Manuela; Brenmoehl, Julia; Schröder, Ina; Willenberg, Holger S.; Reincke, Martin; Zettl, Uwe Klaus (Frontiers in Endocrinology, 2020)
In patients suffering from multiple sclerosis (MS), intrathecal injection of triamcinolone acetonide (TCA) has been shown to improve symptoms of spasticity. Although repeated intrathecal injection of TCA has been used in a number of studies in late-stage MS patients with spinal cord involvement, no clinical-chemical data are available on the distribution of TCA in cerebrospinal fluid (CSF) or serum. Moreover, the effects of intrathecal TCA administration on the concentrations of endogenous steroids are unknown to date. Therefore, we have quantified TCA and selected endogenous steroids in CSF and serum of TCA-treated MS patients suffering from spasticity. Concentrations of steroids were quantified by LC-MS, ELISA or ECLIA and compared with the blood-brain barrier status, diagnosed with the Reibergram. The concentration of TCA in CSF significantly increased during each treatment cycle up to >5 μg/ml both in male and female patients (p<0.001). Repeated TCA administration also evoked serum concentrations of TCA up to >30 ng/ml (p<0.001) and severely depressed serum levels of cortisol and corticosterone (p<0.001). In addition, concentrations of circulating estrogen were significantly suppressed (p<0.001). Due to the potent suppressive effects of TCA on steroid hormone concentrations both in the brain and in the periphery, we recommend careful surveillance of adrenal function following repeated intrathecal TCA injections in patients.